Integration of Gamelan Ethnophysics E-Module to Improve Science Literacy of Sound Wave Materials - Siti Nur Aisah; Adrian Bagas Damarsha; Nadi Suprapto; Eko Hariyono; Nina Fajriyah Citra (National Dong Hwa University, 2025)
Quality education is characterized by the good science literacy skills of students. However, PISA results show that the science literacy of students in Indonesia is still low, which is caused by less interesting learning and a lack of interactivity. One relevant solution is to develop contextual and interactive physics learning tools by integrating local wisdom. Therefore, this study aims to develop and test the validity of the physics module based on gamelan local wisdom and determine the response of students to its use to improve science literacy: This research employed the Research and Development approach utilizing the ADDIE framework, which includes Analysis, Design, Development, Implementation, and Evaluation. The product developed was a physics e-module integrated with Gamelan local wisdom which was validated by experts and tested on students. Results: The module obtained a very valid category from the aspects of content, language, and design. Learners' responses showed that the module was interesting, easy to understand, and improved science literacy skills. Novelty: The integration of gamelan as a form of ethnophysics in the physics module provides a contextual learning experience and encourages the preservation of local culture. This study analyzed the validity and students' response to the physics module based on gamelan.